Constructing a strategy to improve indonesian regency road performance using balanced scorecard - Siswanto, H. (GEOMATE International Society, 2020)
According to its administrative status, Indonesian road network system can be classified into national, provincial, and district (regency) roads. Although there has been continuous improvement of road conditions in Indonesia, district (regency) roads in Indonesia show the worst condition within the Indonesian road network system compared to that of provincial and national roads. As part of the effort to improve the condition, this study is focussed on formulating a strategy to improve district road condition by using balanced scorecard method (BSC). Analytical Hierarchy Process (AHP) was utilised in the weighting of strategic targets. Data was collected through questionnaires distributed to respondents from stakeholders of Public Works Department in seven districts in East Java Province, Indonesia. The result of this study indicates that, according the strategic targets to improve district roads performance, road user (customer) perspective is ranked as highest priority (34.4); Followed by training and development (25.8), financial (20.4), and internal business process perspectives (19.4). Copyright Â© Int. J. of GEOMATE. All rights reserved, including the making of copies unless permission is obtained from the copyright proprietors.